The equation x 2 + b x + c = 0 has distinct roots. If 2 is subtracted from each roots, the results are the reciprocal of the original roots. Then what is the value of b 2 + c 2 ?
Note that b , c are real numbers.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Gosh! Never realized this was so easy!!!!!!!!!!!!!
b = (-2) Great way to solve though 👍🏼
Let the two roots of the equation be α and β . We have that α − 2 = α 1 , and that β − 2 = β 1 .
Putting everything over a common denominator gives α α 2 − 2 α − 1 = 0 . Due to the Zero Product Property , α 2 − 2 α − 1 = 0 .
Since α is a root of our original equation, we know α 2 + b α + c = 0 , and this, in turn, is equal to α 2 − 2 α − 1 = 0 . The same can be achieved with β .
As coefficients in two equal polynomials must also be equal , b = − 2 , and c = − 1 . b 2 + c 2 = − 2 2 + − 1 2 = 5 . □
Nice solution but can we equate the value of alpha from the quadratic equation we obtained for alpha and beta and after getting those use vieta's formulae to get the answer.I used this method correct me if i am wrong.
Let r 1 & r 2 be the roots of the equation, so r 1 + r 2 = − b and r 1 r 2 = c by Vieta's formulas.
We know that.... r 1 − 2 = r 1 1 a n d r 2 − 2 = r 2 1 ⇒ r 1 − r 1 1 = 2 → ( 1 ) r 2 − r 2 1 = 2 → ( 2 )
Setting ( 1 ) = ( 2 ) lets us find the value for c , which is − 1 . Then to find b we add our 2 equations....
( 1 ) + ( 2 ) = r 1 + r 2 − ( r 1 1 + r 2 1 ) = 4 = r 1 + r 2 − ( r 1 r 2 r 1 + r 2 ) = 4 = ( r 1 + r 2 ) ( 1 − r 1 r 2 1 ) = 4
Substituting the value for c in for r 1 r 2 and simplifying, we find that b = − 2 . So b 2 + c 2 = ( − 2 ) 2 + ( − 1 ) 2 = 5 .
Problem Loading...
Note Loading...
Set Loading...
Let the roots of the equation be, α = 2 − b ± b 2 − 4 c
Then, α − 2 = α 1
⇒ α 2 − 2 α − 1 = 0
⇒ α = 2 2 ± 4 + 4
Since α are the roots, therefore, b = 2 and c = − 1 .
⇒ b 2 + c 2 = 2 2 + ( − 1 ) 2 = 5